Intractable Itch in Atopic Dermatitis: Causes and Treatments - Yoshie Umehara; Chanisa Kiatsurayanon; Juan Valentin Trujillo-Paez; Panjit Chieosilapatham; Ge Peng; Hainan Yue; Hai Le Thanh Nguyen; Pu Song; Ko Okumura; Hideoki Ogawa; François Niyonsaba (Biomedicines, 2021)
Itch or pruritus is the hallmark of atopic dermatitis and is defined as an unpleasant sensation that evokes the desire to scratch. It is also believed that itch is a signal of danger from various environmental factors or physiological abnormalities. Because histamine is a well-known substance inducing itch, H1-antihistamines are the most frequently used drugs to treat pruritus. However, H1-antihistamines are not fully effective against intractable itch in patients with atopic dermatitis. Given that intractable itch is a clinical problem that markedly decreases quality of life, its treatment in atopic dermatitis is of high importance. Histamine-independent itch may be elicited by various pruritogens, including proteases, cytokines, neuropeptides, lipids, and opioids, and their cognate receptors, such as protease-activated receptors, cytokine receptors, Mas-related G protein-coupled receptors, opioid receptors, and transient receptor potential channels. In addition, cutaneous hyperinnervation is partly involved in itch sensitization in the periphery. It is believed that dry skin is a key feature of intractable itch in atopic dermatitis. Treatment of the underlying conditions that cause itch is necessary to improve the quality of life of patients with atopic dermatitis. This review describes current insights into the pathophysiology of itch and its treatment in atopic dermatitis.